2022
DOI: 10.1155/2022/4754764
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Factors Influencing Coal Fracturing Range Caused by Liquid Carbon Dioxide Phase Transition

Abstract: Liquid carbon dioxide phase transition fracturing technology (LCPTF) is an effective method to increase coal seam permeability, but there are many factors that affect the fracturing effect. Blasting pressure, vent diameter, and blasting time are important factors that affect the fracturing effect. However, very limited studies were performed in this regard. Therefore, in this paper, a multifield coupled model for fracturing coal bodies by LCPTF is established; the effect of blasting pressure, vent diameter, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…An escalation in blasting pressure has multiple implications, which ultimately result in a surge in crack propagation speed. First, the high-pressure dynamic impact produces longer initial dynamic cracks, which in turn curtails the propagation length of quasi-static gas wedge cracks . Second, the high-pressure dynamic impact reduces the mechanical strength of the sample, thereby facilitating crack propagation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An escalation in blasting pressure has multiple implications, which ultimately result in a surge in crack propagation speed. First, the high-pressure dynamic impact produces longer initial dynamic cracks, which in turn curtails the propagation length of quasi-static gas wedge cracks . Second, the high-pressure dynamic impact reduces the mechanical strength of the sample, thereby facilitating crack propagation.…”
Section: Resultsmentioning
confidence: 99%
“…First, the high-pressure dynamic impact produces longer initial dynamic cracks, which in turn curtails the propagation length of quasi-static gas wedge cracks. 39 Second, the high-pressure dynamic impact reduces the mechanical strength of the sample, thereby facilitating crack propagation. Lastly, the quasi-static pressure increases after high-pressure dynamic impact, leading to faster crack propagation.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to hydraulic fracturing that characterized by quasi-static loading and typical two-wing straight fracture planes, SCS fracturing has the following advantages in the stimulation of HDR reservoirs: ① Instantaneous dynamic shock loading can crush the near-wellbore zone dramatically (zone A as shown in Fig. 15) to create a complex interconnected fracture network with high conductivity in a certain distance (a few meters to tens of meters as reported by Hu et al [39] ) around the wellbore. This zone significantly reduces the skin factor and corresponding flow resistance near the wellbore, enhancing the injection capacity and production rate of heat extraction fluid.…”
Section: Discussionmentioning
confidence: 99%
“…Jia et al 88 used LS-DYNA software to simulate and analyze the effects of physical parameters of coal seams and borehole diameter on the effect of liquid CO 2 phase change fracturing on coal seams, and the results show that there are positive relationships between the fracturing effect of coal seams and the pressure, modulus of elasticity, and borehole diameter, there are negative relationships with the geopathic stress and compressive strength, and the process is nearly irrelevant to the tensile strength. Hu et al 89 tablished a multiphysical field coupling model and found that the longer the liquid CO 2 phase transition cracking time, the greater the fracturing radius. After the fracturing, the fracturing radius remained almost unchanged, and the greater the gas pressure, the more significant the increase in the coal seam permeability.…”
Section: Current Status Of Research On Anhydrous Coal and Gas Outburs...mentioning
confidence: 99%